On local antimagic vertex coloring of corona products related to friendship and fan graph - Zein Rasyid Himami; Denny Riama Silaban (Indonesian Combinatorial Society (InaCombS), 2021)
Let G=(V,E) be connected graph. A bijection f : E → 1,2,3,..., |E| is a local antimagic of G if any adjacent vertices u,v ∈ V satisfies w(u)≠ w(v), where w(u)=∑e∈E(u) f(e), E(u) is the set of edges incident to u. When vertex u is assigned the color w(u), we called it a local antimagic vertex coloring of G. A local antimagic chromatic number of G, denoted by χla(G), is the minimum number of colors taken over all colorings induced by the local antimagic labeling of G. In this paper, we determine the local antimagic chromatic number of corona product of friendship and fan with null graph on m vertices, namely, χla(Fn ⊙ K_m) and χla(f(1,n) ⊙ K_m).